The sex of things : gender and consumption in historical perspective - De Grazia, Victoria; Furlough, Ellen, 1953- (University of California Press, 1996)
For centuries, women have been caricatured as consummate shoppers, relegated to provisioning the household, and fetishized as objects of advertising. This wide-ranging volume of thirteen original essays illuminates the development of modern consumption practices, gender roles, and the sexual division of labor in both the United States and Europe. Drawing on social, economic, and art history as well as cultural studies, these essays consider commodities from bread and potatoes, cosmetics, home appliances, and the dandy's suit to social welfare handouts, movie melodramas, and pornographic picture cards. With extensive introductions and an annotated bibliography, this volume advances a new research field and the vital social and cultural issues at stake in its progress.